Prevalence, species identification, and antibiotic resistance of Staphylococci in dogs visiting veterinary clinics in Vietnam. - Nguyen Thi Lan Anh; Nguyen Vu Thuy Hong Loan; Nguyen Thuy Y Vi; Dao Huyen Tran; Luu Thi Thanh Hang; Sandra Steele; Lam Thanh Nguyen (PLoS ONE)
Staphylococci are important commensal and opportunistic bacteria found in various animals, including dogs and humans. The emergence of antibiotic-resistant Staphylococci is a growing global concern, including in Vietnam. This study aimed to investigate the prevalence, species distribution, and antibiotic-resistance profiles of Staphylococci isolated from dogs visiting veterinary clinics in Vietnam. A total of 309 Staphylococcus strains were isolated from 410 nasal and skin samples collected from both healthy and diseased dogs between December 2021 and December 2023 in Ho Chi Minh city. The isolation rate of Staphylococcus spp. was 71.2% (95% confidence interval [CI]: 66.6%-75.6%), with 78.9% (95% CI: 73.6%-83.7%) in diseased dogs, 56.9% (95% CI: 48.4%-65.2%) in healthy dogs, 80.1% (95% CI: 74.3%-85.1%) in skin samples, and 60.3% (95% CI: 52.9%-67.5%) in nasal samples. Species identification indicated that S. pseudintermedius was dominant, followed by S. aureus. Other species identified included S. epidermidis and S. schleiferi. Antibiotic susceptibility testing showed complex resistance patterns. Approximately 91.3% of isolates were resistant to at least one antibiotic, and 60.5% were multidrug-resistant (resistant to three or more antibiotics). A total of 215 antibiotic-resistance phenotypes were observed, with 85 phenotypes showing resistance to more than ten different antibiotics. Isolates from diseased dogs exhibited higher antibiotic-resistance rates than those from healthy dogs. Several antibiotic-resistance genes were identified, with aacA-aphD being the most prevalent, followed by tetK, gyrA, mecA, msrA, dfrA, and ermA. These findings highlight the widespread presence of antibiotic-resistant Staphylococci in dogs and emphasize the necessity for ongoing surveillance of antibiotic-resistance evolution in animals and its implications for human health.